2022-RA-963-ESGO The impact of low-volume metastasis on disease-free survival of women with apparent early-stage endometrial cancerunderwent sentinel node biopsy: a retrospective study. (20th October 2022) - Buda, Alessandro A; Paniga, Cristiana; Taskin, Salih; Mueller, Michael; Zapardiel, Ignacio; Fanfani, Francesco; Puppo, Andrea; Papadia, Andrea; de Ponti, Elena; Turan, Hasan; Perotto, Stefania; Gungor, Mete; et al.
Abstract : Introduction/Background: We assessed the impact of low-volume metastasis (LVM) on disease-free survival (DFS) of women with apparent early-stage endometrial cancer (EC) that underwent sentinel lymph node (SLN) mapping. Methodology: Patients with preoperative diagnosis of EC were retrospectively collected from eight referring institutions. Results: 1428 patients were included in this analysis. One hundred and eighty-six patients (13%) had lymph node involvement. Forty-eight percent of positive sentinel lymph nodes had macrometastasis (MAC), 31.3% micrometastasis (MM), and 20.5% isolated tumor cells (ITC). Fifty-seven percent of patients with positive lymph nodes didn't receive adjuvant therapy. At a median follow-up of 23.7 months, 114 women recurred (8%). Recurrence rate was 28%, 12% and 19% in women with MAC, MM, and ITC, respectively. Patients with MAC in the SLN's had a worse prognosis in terms of disease-free survival (DFS) compared to patients with negative nodes or with LVM (P< .0001). The type of nodal metastasis did not impact on DFS of patients (HR1.58; p= 0.094). The multivariate analysis showed a difference in DFS when the negative subgroup of women was added to the model (HR 1.26; p= 0.014). Conclusion: In our retrospective study we found that women with MAC have a worse disease DFS compared to women with negative nodes, while the patients with LVM might be considered at intermediate risk. The type of nodal metastasis in the SLN nodes seems to not significantly impact on the risk of recurrence. In the era of molecular profiling, ongoing studies will better clarify the value of SLN biopsy and the of performing a pelvic and/or aortic lymphadenectomy in early-stage EC.